Penggunaan Keigo dalam Bahasa Jepang untuk Bisnis - Yuniarsih Yuniarsih; Sudjianto Sudjianto; Fitri Fauziyyah (Chi'e: Journal of Japanese Learning and Teaching, 2022)
This study aims to describe politeness when performing speech acts in business using Leech's theory of politeness principles. The research object is the speech data of business people when interacting within one company or between companies. The research method used is descriptive qualitative research because it aims to describe linguistic phenomena naturally. Politeness is a rule of behavior determined and mutually agreed upon by a particular community, so politeness is also an agreed requirement in social behavior. In their interactions, business people must be polite. This is reflected in his speech with the perpetrator of the speech act. The study results indicate that in addition to being grammatically correct in terms of the form of Keigo itself, it must pay attention to language politeness. In general, using Keigo in business conversations in various social speech contexts emphasizes simplicity and respect. In addition, it also prioritizes wisdom and sympathy.